PENGARUH PENAMBAHAN SENYAWA BIOAKTIF DARI ALGA COKELAT (Sargassum sp.) PADA PAKAN TERHADAP HISTOLOGI USUS DAN HATI BENIH IKAN PATIN SIAM (Pangasius hypopthalmus) - Adinda Nurkholifah; Fittrie Meyllianawaty Pratiwy; Roffi Grandiosa Herman; Iskandar Iskandar (Jurnal Perikanan Unram, 2024)
Addition of Sargassum sp. into feed as a feed supplement is one effort that can be done to increase fish growth and immunity. This research aims to determine the effect of adding bioactive compounds from Sargassum sp. extract in feed on the health picture of Siamese catfish through structural changes that occur in the intestines and liver. Fish observations were carried out for 40 days. The results obtained regarding the survival rate (SR) value of Siamese catfish seeds show that there is no difference or has the same percentage, namely 100%. The results of observations on the histopathology of intestinal organs analyzed in a comparative descriptive manner showed that Siamese catfish fry were fed with Sargassum sp. extract experienced damage than fish seeds fed without the addition of Sargassum sp. extract (control). The damage that occurs includes leukocyte infiltration (IfL), necrosis (Ne), goblet cell proliferation (Psg), hyperplasia (Hpl), and hemorrhage, with a damage score analyzed using the semiquantitative scoring method, namely 1. Damage to the liver, namely experiencing congestion in the blood vessels.